Role-Playing Between Environmental Pollutants and Human Gut Microbiota: A Complex Bidirectional Interaction - Giambò, Federica; Costa, Chiara; Teodoro, Michele; Fenga, Concettina (Frontiers in Medicine, 2022)
There is a growing interest in the characterization of the involvement of toxicant and pollutant exposures in the development and the progression of several diseases such as obesity, diabetes, cancer, as well as in the disruption of the immune and reproductive homeostasis. The gut microbiota is considered a pivotal player against the toxic properties of chemicals with the establishment of a dynamic bidirectional relationship, underlining the toxicological significance of this mutual interplay. In fact, several environmental chemicals have been demonstrated to affect the composition, the biodiversity of the intestinal microbiota together with the underlining modulated metabolic pathways, which may play an important role in tailoring the microbiotype of an individual. In this review, we aimed to discuss the latest updates concerning the environmental chemicals–microbiota dual interaction, toward the identification of a distinctiveness of the gut microbial community, which, in turn, may allow to adopt personalized preventive strategies to improve risk assessment for more susceptible workers.